Odpowiedź :
[tex]a) 4x^2 + x y = x(4x + y)[/tex]
[tex]b) 2x^3 - 12xy = 2x(x^2 - 6y)[/tex]
[tex]c) 3xy -xyz = xy (3 - z)[/tex]
[tex]d) 6pq + 18p^2q = 6pq(1 + 3p)[/tex]
[tex]e) a^2b + 3a^2b^2 -a^3b = a^2b(1 + 3b - a)[/tex]
[tex]f) 4x^2y^2 - 5x^3y^2 +2x^2y^3 = x^2y^2(4 - 5x + 2y)[/tex]
Odpowiedź:
[tex]a)\ \ 4x^2+xy=x(4x+y)\\\\b)\ \ 2x^3-12xy=2x(x^2-6y)\\\\c)\ \ 3xy-xyz=xy(3-z)\\\\d)\ \ 6pq+18p^2q=6pq(1+3p)\\\\e)\ \ a^2b+3a^2b^2-a^3b=a^2b(1+3b-a)\\\\f)\ \ 4x^2y^2-5x^3y^2+2x^2y^3=x^2y^2(4-5x+2y)[/tex]